'Unzipping' of twin lamella in nanotwinned nickel nanowires under flexural bending. Issue 1 (2nd January 2018) - Wang, Binjun; Zhang, Hongti; Lou, Jun; Lu, Yang
ABSTRACT: We report the fabrication of nickel nanowires with parallel growth-twin structures ('twin lamella' along the wire axis) by electrochemical deposition, and demonstrate an interesting twin 'unzipping' phenomenon in such nanotwinned nanowires under bending. Through in situ TEM, we found that 'unzipping' of twin lamella was achieved by gradually increasing twin spacing along the wire axis via a layer-by-layer twin boundary migration process. Molecular dynamics simulations suggest that partial dislocation slip is responsible for activating the 'unzipping', with a multi-step-process involving dislocation loop initiation, expansion and partially annihilation. Our work could provide new insights into the deformation mechanisms of nanotwinned 1-D metallic nanostructures. GRAPHICAL ABSTRACT: IMPACT STATEMENT Nickel nanowires with parallel-twin structures were fabricated and demonstrated an interesting twin lamella 'unzipping' behavior upon flexural bending, which provides new insights into the deformation mechanisms of nanotwinned metallic materials.